Enhancing takaful performance from quality of islamic leader's perspective: A case of Malaysian takaful operator - Wan Norhayate, Wan Daud; Fakhrul Anwar, Zainol; Marlisa, Abdul Rahim; Abdul Ghafar, Ismail (2016)
Based on the continuing growth of Takaful demand around the world, there is an even more pressing need to develop the Islamic leaders’ qualities and competencies on a global basis. Yet, despite this growth, leaders’ qualities has become a major problem facing by the Takaful operators in Malaysia. Very little attention has been directed to the qualities of Islamic leaders to improve the business performance. Based on this reality, it is of interest to examine whether Islamic leaders’ qualities affect Takaful performance in Malaysia. This study focuses on the relationship between qualities of Islamic leaders’ truthfulness (al-sidq), trust (amanah), knowledge (fathonah), and communication (tabligh) and organizational performance of Takaful operators in Malaysia. Study attempts to achieve three objectives. First, to determine the qualities of Islamic leaders in Malaysian Takaful industry. Second, to analyze the effect of Islamic leaders’ qualities on Takaful performance in Malaysia. Third, to develop a model of qualities of Islamic leaders and Takaful performance in Malaysia. This study used quantitative research study. The respondents involved were the staff (managerial level) of Takaful operators in Malaysia. Seven organizations from the Takaful industry in Malaysia participated in the study. A total of 110 questionnaires were distributed and 59 responded in which they were analyzed. This study uses the quantitative approach and employed SPSS Windows Software (version 19.0). The statistical tools used to analyze the descriptive statistics, factor analysis, reliability analysis and multiple regressions. The results of this study have provided a significant contribution to the Malaysian Takaful operators in improving their performance from both theoretical and practical aspects.